JUDICIAL DEFIANCE UNMASKED: SEMA 3/2023 vs MK 34/2013 - Fransiscus Nanga Roka,; Yovita Arie Mangesti,; Erny Herlin Setyorini, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research aims to explore whether SEMA NO. 3/2023 indeed functions as a legal constitutional dialogue or an administrative constitutional defiance against binding MK Decision NO. 34/2013. The research problem is twofold, drawn doctrinal: is the reintroduction of PK limitation through SEMA an administrable implementation doctrinally applicable, or it reverses the similar administrative reversibility of constitutional content determined by the Court? Conceptual disambiguation is performed based on a normative juridical method, combined with a doctrinal comparative method. Systematic document study with constitutional text extraction and hierarchical norm-testing are instrumentalized in determining whether the problem is interpretive disagreement or bureaucratic contravention. The results of the research paper found that SEMA3/2023 does not operate as hermeneutic interpretation but as operational bureaucratic command in MK jurisprudence bypassance, and consequently produces constitutional consequence without constitutional adjudication. The key-findings of the research procure found that the normative effect of SEMA 3/2023 doctrinally functions as an administrative constitutional reversal since it reopens the legal path that the Constitution Court has already closed. Comparative analysis with Germany, Italy, and Singapore indicates that civil-law jurisdictions in their design structurally bar administrative constitutional re-constitution of established constitutional meaning. The research thus concludes that SEMA 3/2023 is not a judicial dialogue but an administrative constitutional sabotage in the dual apex configuration formalism of Indonesia.